Dinâmica de campos escalares fora do equilíbrio - Farias, R. L. S [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
We consider the nonequilibrium dynamics of the formation of a condensate in a spontaneously broken'lâmbda fi' POT. 4' relativistic quantum scalar field theory. The equation of motion of the corresponding order parameter is a stochastic Ginzburg-Landau-Langevin equation, derived from the quantum effective action of the theory. This equation incorporates additive and multiplicative noises, which allows to study the role of fluctuation and dissipation in the formation process of the condensate. The effective action is derived using the real time formalism of finite temperature quantum field theory for both the symmetric and spontaneously broken phases. For the calculation of the effective action we employ the nonperturbative method known as optimized perturbation theory and compare the corresponding results with the usual perturbation theory in the coupling constant. Numerical results for the solutions of the Ginzburg-Landau-Langevin equations are obtained through large scale mumerical simulations on a three-dimensional spatial lattice. Particular attention is payed to the renormalization of ultraviolet divergences that appear in the simulations of the equations on a spatial lattice

Consideramos a dinâmica de não equilíbrio da formação de um condensado numa teoria quântica de campos relativística descrevendo campos escalares com acoplamento 'lâmbda fi' POT. 4' com quebra espontânea de simetria. A equação de movimento do correspondente parâmetro de ordem é uma equação estocástica do tipo Ginzburg-Landau-Langevin, a qual é derivada a partir da ação efetiva quântica da teoria. Esta equação incorpora ruídos aditivo e multiplicativo, o que permite estudar o papel da flutuação e da dissipação no processo de formação do condensado. A ação efetiva é derivada empregando o formalismo de tempo real da teoria de campos à temperatura finita tanto para fase simétrica como para fase espontaneamente quebrada da teoria. No cálculo da ação efetiva empregamos um método não perturbativo conhecido como teoria da perturbação otimizada até a ordem de três loops, e comparamos com os correspondentes resultados obtidos com a usual teoria de perturbação na constante de acoplamento. Resultados numéricos para as soluções das equações de Ginzburg-Landau-Langevin são obtidos de simulações numéricas de larga escala numa rede espacial em três dimensões. Uma atenção particular é dedicada à renormalização das divergências ultravioletas que aparecem nas simulações destas equações numa rede
Keywords: Teoria de campos (Física); Transformações de fase (Física estatística); Perturbação (Matematica); Field theory (Physics)